ECONOMIC RELATIONS IN THE FIELD OF WOMEN’S EMPLOYMENT - Xoliqov , Sulaymon O‘tkir ug‘li (Innovative Development in Educational Activities, 2023)
This groundbreaking article provides a comprehensive examination of economic relations within the context of women’s employment. With a keen focus on the current state of affairs, it sheds light on the complexities surrounding gender equality, work opportunities, and societal norms. The authors delve into the multifaceted challenges faced by women in the workforce, highlighting persistent gender-based discrimination, wage gaps, and limited access to leadership positions. They present compelling evidence and statistical data to underscore the considerable economic potential that remains untapped due to systemic barriers and biases. Furthermore, the article explores the impact of cultural, social, and political factors on women’s economic empowerment. It critically analyzes policy frameworks, workplace practices, and educational systems to identify areas for improvement and propose viable solutions. The authors emphasize the importance of creating inclusive environments, equal opportunities, and supportive policies to foster the participation and advancement of women in the labor market.